2022
DOI: 10.1002/csr.2420
|View full text |Cite
|
Sign up to set email alerts
|

The sustainability orientation in the wine industry: An analysis based on age as a driver

Abstract: Few studies probe small and medium enterprises (SMEs) in the context of sustainability. Thus, this study examines the sustainability orientation in SMEs and its impact on financial performance, considering the 'ageing effect'. It employs a sample of Italian SMEs operating in the wine sector, using a survey questionnaire to collect qualitative and quantitative data for analysis. Accordingly, although sustainability remains typically unembedded within such SMEs, when it is embedded, a positive correlation with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 115 publications
1
4
0
Order By: Relevance
“…One possible reason could be that SMEs have observed that, following the implementation of sustainability plans, they achieve higher financial gains than the resources allocated for sustainable investments. This finding is consistent with [69,134,135], where enterprises not only perceive the social importance of sustainable business activities intensely but also demonstrate an increased interest in implementing sustainability plans.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…One possible reason could be that SMEs have observed that, following the implementation of sustainability plans, they achieve higher financial gains than the resources allocated for sustainable investments. This finding is consistent with [69,134,135], where enterprises not only perceive the social importance of sustainable business activities intensely but also demonstrate an increased interest in implementing sustainability plans.…”
Section: Discussionsupporting
confidence: 86%
“…As the first objective of this study is to identify the impact of independent variablese-marketing orientation (EMO), sustainability orientation (SO), and technology orientation (TO)-on the dependent variable online SME business performance (OBP), we believe that PLS-SEM is appropriate for analyzing the construct model. Therefore, previous marketing studies with similar latent variables were reviewed to analyze the data using PLS-SEM [42][43][44][45][46][68][69][70][91][92][93][94][95]. Multi-group analysis (PLS-MGA) was deemed suitable for examining significant differences between e-commerce intensity groups in the constructions EMO → OBP, SO → OBP, and TO → OBP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study conducted by Broccardo et al (2023) demonstrates that the age of business in the wine industry is a significant factor that might account for variations in sustainability orientation and its influence on the financial performance of Italian small and medium-sized enterprises.…”
Section: Indicators and Performance Measurementmentioning
confidence: 99%